An Inquiry into the Nature and Causes of Financial Disasters - Prabhu Sankar, Sai Swathi (2017)
ABSTRACT This paper introduces a general model of why financial system disasters occur. The first element of our model starts with the consideration of the analogy of Newtons Law of Inertia. Because of market makers activity and objective, price trends in the market tend to follow Newtons First Law. Therefore, a single event can give rise to a trend. Hence, we consider logical connections among events that lead to an outcome. Mackie’s definition of causation along with the model of the tortoise by Young et al., (2004), we learn that every financial disaster has a trigger event. When the probability of crash increases, people are likely to switch from one equilibrium to another which results in a disaster. When there is a switch between equilibriums, the system can follow Maxwell’s Rule or the Delay Rule. If the system follows the Delay Rule then we would have fewer catastrophes but more disastrous ones than if we followed Maxwell’s Rule. Even if we can induce the system to follow the Delay Rule, we will still have disasters. Hence, we could put measures in place to protect vulnerable people from the outcomes of disasters.